Root Evaluation of Slope Protection Vegetation Characteristic Indexes on Expansive Soil in Nanning City Based on Entropy Value Method - Xu Yingzi; Zhu Qiaosheng; Huang Xiao (Shuitu baochi tongbao)
[Objective] The protective effect of plants on the slope of an expansive soil was evaluated in order to provide a scientific reference for the selection of protective vegetation on the slope of expansive soils. [Methods] Eight common plants were selected from the herbaceous vegetation in the expansive soil area in Nanning City, Guangxi Zhuang Autonomous Region, and their overall root characteristics and stratified root characteristics were extracted. The four indexes of stratified root characteristics (root length, root surface area, root diameter, and root volume) were calculated. The entropy method was used to assign weights to the four characteristic indexes of the root system, and the advantages and disadvantages of the slope protection effect of vegetation root systems were evaluated comprehensively based on the weight of different characteristic indexes. [Results] The results showed that the root diameter of vegetation ranged from 0.25 mm to 0.55 mm, and there was little change with depth. Root length, root surface area, and root volume in shallow soil of 0—5 cm layer) accounted for 50.0%~85.4% of the entire depth range, and decreased sharply with increasing soil depth. Root length, root surface area, and root volume had obvious advantages over the entire depth range. The weight coefficients of root length, root surface area, root diameter, and root volume were 0.310 0, 0.243 2, 0.165 4, and 0.281 5, respectively. The comprehensive evaluation value was the highest for Bidens pilosa. (0.916), followed by Festuca elata (0.761). The lowest value was observed for Lolium perenne (0.110). [Conclusion] Based on the comprehensive analysis of different index weights, the rating of Bidens pilosa was the highest, and therefore, this species is the most suitable for slope protection in the expansive soil area of Nanning City.